PELATIHAN KARTU ANGKA BERGAMBAR DALAM MENINGKATKAN PERKEMBANGAN KOGNITIF ANAK USIA PRA SEKOLAH (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2022)
Inappropriate learning methods can cause a decrease in children's learning motivation, the lack of understanding of teachers and parents in improving cognitive development in children can result in poor child development. To overcome this problem, appropriate intervention is needed. As the practice of the Tridarma of higher education, a lecturer must do community service. One of the services that has been carried out is a community service activity with the title "Training of illustrated number cards in the cognitive development of pre-school age children". In this case, the target achieved is the high participation of students in games with picture number cards and increasing knowledge of teachers and parents about cognitive development in children through picture number card games. The method used is to screen knowledge about cognitive development, then carry out training on number cards. pictorial. Time : conducted for 2 days, Place : in RA/TK in Mranggen sub-district. Instruments: cards, illustrated numbers, training materials, demonstrations, and questionnaires. The result of this service is that students participate in picture number card games and there is an increase in the knowledge and skills of teachers and parents regarding picture number cards.